2008
DOI: 10.1073/pnas.0801621105
|View full text |Cite
|
Sign up to set email alerts
|

Conformal geometry of the retinal nerve fiber layer

Abstract: The nerve fiber layer of the human retina is made up of the retinal segments of ganglion cell axons. Its geometry can be described mathematically as a fibration of a 2D domain: a partition of a certain region into smooth curves. Here, we present a simple family of curves that closely models the observed geometry of the nerve fiber layer. For each retina, the pattern depends on 2 parameters, A and B: A computer program determines A and B for a given retina and the theory matches the retina with a standard devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Several of these mathematical RNFL models exist. 11,12,14 However, the complexity of these models may be very different. For example, an axial model is very simple but quickly becomes inaccurate with increasing distance from the optic nerve head (ONH), while a model with many parameters may be able to largely capture normal morphologic variation between different eyes.…”
Section: Model and Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Several of these mathematical RNFL models exist. 11,12,14 However, the complexity of these models may be very different. For example, an axial model is very simple but quickly becomes inaccurate with increasing distance from the optic nerve head (ONH), while a model with many parameters may be able to largely capture normal morphologic variation between different eyes.…”
Section: Model and Datamentioning
confidence: 99%
“…Airaksinen et al 11 optimized the shape parameters A and B on observed nerve fiber bundle patterns in fundus photographs.…”
Section: Model and Datamentioning
confidence: 99%
See 3 more Smart Citations